IMPLEMENTASI ASSESMEN KURIKULUM MERDEKA DI SD NEGERI 03 PONTIANAK SELATAN - Munawar, Munawar; Hairida, Hairida; Hartoyo, Agung (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2024)
This research aims to describe the implementation of Independent Curriculum Assessment at SD Negeri 03 Pontianak Selatan. The research method applied is descriptive with a qualitative approach. The tools which is used to collect data are interview sheets, questionnaires and documentation. The data analysis technique used is according to Miles and Hubermen with stages of data reduction, data presentation and drawing conclusions. Based on the research results, information was obtained that 1) The assessment planning carried out in schools is: a) The teacher analyzes Learning Achievements (CP) and determines the Learning Goal Flow (ATP) together, b) The teacher determines the Learning Goals and adjusts them to the students' abilities , c) The teacher determines the type of assessment and arranges the implementation schedule. 2) diagnostic assessments are carried out at the beginning of the semester, formative assessments at the end of learning and summative assessments after completing a particular topic or material. 3) 60% of teachers have used the assessment results to improve the learning process. 4) the assessment carried out influences the results of the school education report card. Literacy achievement increased by 16.57 from 83.33 to 100. Meanwhile, the numeracy component achievement experienced a significant increase of 36.67 from 63.33 to 100.